Studi Fasa dan Sifat Termal Lantanum Oksida Berbasis Monasit - Dewi, Sari Hasnah; Adi, Wisnu Ari; Suyanti (BRIN Publishing, 2019)
Rare earth elements (REE) in Indonesia have great potency, mainly from monazite mineral. Monazite is a combination of REE-U/Th-phosphate elements which is associated with tin deposit and radioactive elements. Through BATAN incorporated program, monazite mineral is processed to become more economically valuable materials. Lanthanum (La) is a metal element, part of REE group, which has excellent properties for pigment and electromagnetic absorber. The purpose of this study is to obtain information related to the effect of calcination in high temperature on the product of monazite’s REE hydroxide (RE(OH)3) processing pilot plant, specific on La2(C4O4)3 for Certified Reference Material (CRM) La2O3 making. The weighed material is calcined on combustion boat by using a furnace at heating temperature of 1,000 OC and 1,300 OC. Thermal decomposition is analyzed by using Thermogravimetric analysis (TGA). Material phase formation is analyzed by using X-Ray Diffraction (XRD) method. XRD analysis shows the material in final phase has been transform to 28.76 % La2O3 and 71.24 % La(OH)3.